Indaquassin A and B: Quassinoids from Quassia indica - Koike, Kazuo; Ohmoto, Taichi (Phytochemistry (Oxford), 1993)
Two novel quassinoids, indaquassins A and B, were isolated from the bark of Quassia indica. Their structures were determined by various 2D NMR analyses. The absolute stereostructures of indaquassins A and B were unambiguously determined by the non-empirical exciton chirality circular dichroism method carried out on their p-bromobenzoate derivatives. Indaquassin B is reported here for the first time as a new class of rearranged C 20-quassinoid.